Pendampingan E-Marketing Melalui Media Sosial Instagram Pada Usaha Mikro Dusun Banjaragung, Desa Banjaragung, Jombang - Windi Putri Lestari; Kusuma Wardhani Mas’udah; Eka Restu Justitian; Intan Novitasari; Shafira Zalfa Adiningrum (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
In the globalization era, the fast-paced marketing competition is a challenge for micro businessmen to compete and survive. The rapid flow of technology and information development give an impact and also opens up the potential that can be utilized in developing micro-enterprises to expand marketing. E-marketing takes the role to make convenience both for sellers to offer their products, as well as for consumers to buy the desired product. E-marketing assistance for product marketing through Instagram social media is carried out to help micro-enterprises in Banjaragung Hamlet, Banjaragung Village, Jombang Regency. This study uses a qualitative descriptive method. Qualitative descriptive is a type of research approach in which the results are described and explained in sentences. This product marketing assistance through Instagram social media was carried out to help micro-enterprises in Banjaragung Hamlet, Banjaragung Village, Jombang Regency. The result of this assistance is that micro businessmen have the skills to innovate in marketing products through Instagram social media, which is a trending platform and is widely used in Indonesia. Apart from being a promotional medium, the micro businessmen can also identify the consumer needs and see trends that can be used as the references for product variations.